Pengaruh Efektivitas Sistem Perpajakan dan Motivasi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Empiris pada PT. Proxsis Global Solusi) - Azzahra, Davina; Rumiasih, N.A.; ., Yudiana (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to find out: (1) The effect of the Effectiveness of the tax system on the compliance of individual taxpayers in PT. Proxsis Global Solutions and (2) The Effect of Tax Motivation on Individual Taxpayer Compliance in PT. Proxsis Global Solutions. The population in this study is Individual Taxpayers at PT. Proxsis Global Solutions. The sampling technique is the Accidental Sampling technique. Data collection method with Questionnaire and Observation. The analysis methods used in this study are descriptive analysis, data quality test, classical assumption test, multiple linear regression analysis, determination coefficient and hypothesis test. The results of the study show that: (1) The effectiveness of the tax system has a positive effect on the compliance of individual taxpayers in PT. The Global Proxsis of the Solution, is evidenced by the t-value of the t-table > (3.409 > 1.67469) and the significance value (0.001 < 0.05). (2) Tax motivation has a positive effect on the compliance of individual taxpayers in PT. The proxsis of the Global Solution, is evidenced by the t-value of the t-table > (2.592 > 1.67469) and the significance value (0.012 < 0.05).